2017
DOI: 10.1080/09540261.2017.1282439
|View full text |Cite
|
Sign up to set email alerts
|

The application of deep brain stimulation in the treatment of psychiatric disorders

Abstract: Deep brain stimulation (DBS) is a last-resort treatment for neurological and psychiatric disorders that are refractory to standard treatment. Over the last decades, the progress of DBS in psychiatry has been slower than in neurology, in part owing to the heterogenic symptomatology and complex neuroanatomy of psychiatric disorders. However, for obsessive-compulsive disorder (OCD) DBS is now an accepted treatment. This study first reviews clinical outcomes and mechanisms of DBS for OCD, and then discusses these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 99 publications
(112 reference statements)
1
59
0
5
Order By: Relevance
“…This neuroanatomical model of OCD has formed the basis for neuroanatomically based treatments for OCD, such as deep brain stimulation (DBS). Specific targets in the application of deep brain stimulation (DBS) are striatal areas, including the ventral internal capsule/ventral striatum, the nucleus accumbens, the subthalamic nucleus, the anterior limb of the internal capsule, and the inferior thalamic peduncle (6). DBS has been associated with response rates of up to 60% (7).…”
Section: Advances In Biological Approaches To Treating Resistant/refrmentioning
confidence: 99%
“…This neuroanatomical model of OCD has formed the basis for neuroanatomically based treatments for OCD, such as deep brain stimulation (DBS). Specific targets in the application of deep brain stimulation (DBS) are striatal areas, including the ventral internal capsule/ventral striatum, the nucleus accumbens, the subthalamic nucleus, the anterior limb of the internal capsule, and the inferior thalamic peduncle (6). DBS has been associated with response rates of up to 60% (7).…”
Section: Advances In Biological Approaches To Treating Resistant/refrmentioning
confidence: 99%
“…Active implanted medical devices (AIMDs) based on electrical stimulation such as pacemakers (Gold et al, 2017), spinal cord stimulators (Patel et al, 2017), and cardioverter-defibrillators (Proclemer et al, 2001) have become a standard therapeutic choice to restore healthy neural activity in a wide range of medical conditions (D'Haese et al, 2010). In the brain, deep brain stimulation (DBS) uses electrical stimulation for the treatment of several medically refractory brain disorders, including essential tremor, Parkinson's disease, major depression, dystonia, Tourette syndrome, chronic pain, and obsessive-compulsive disorder (Lefaucheur et al, 2004;Walter and Vitek, 2004;Montgomery and Gale, 2008;Machado et al, 2009Plow et al, 2009;Holtzheimer and Mayberg, 2011;Vitek et al, 2011;Machado and Baker, 2012;Plow et al, 2012;Graat et al, 2017;Clair et al, 2018). Despite their remarkable success, significant limitations are still curtailing the use of AIMDs.…”
Section: Introductionmentioning
confidence: 99%
“…3 Treatment resistance leads to reduced quality of life, [4][5][6] increased risk of suicide, 7,8 and decreased work productivity. 9 Recent studies have shown that up to 60% of patients suffering from treatment-resistant OCD (TR-OCD) respond to deep brain stimulation (DBS), 10,11 up to 41% respond to anterior cingulotomy, and up to 54% respond to anterior capsulotomy. 12 Open-label trials have resulted in 30-50% remission rates for DBS in treatment-resistant MDD (TR-MDD) [13][14][15][16][17][18] although two randomized controlled trials (RCTs) have had conflicting results 19,20 and a recent multisite randomized shamcontrolled trial has failed to demonstrate statistically significant benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanisms of action are not clearly established, but DBS is thought to exert its effects at both neuronal and network levels by increasing neurotransmitter release, modulating neuronal synchronization, and promoting neuroplasticity. 25 Adverse effects of anterior cingulotomy/capsulotomy (AC) and DBS are usually mild and/or transient, 10,11,[25][26][27][28] and unlike older neuroablative techniques such as leucotomies and lobotomies, 29,30 major complications are rare occurrences. 25 While symptom relief and even remission can sometimes be obtained in patients with TR-MDD and TR-OCD, 25,26 there are very few patients undergoing these neurosurgical procedures.…”
Section: Introductionmentioning
confidence: 99%